Impact of ferric carboxymaltose in patient blood management in Portuguese hospitals. (30th September 2020) - Lucas, J; Sousa, P; Sequeira, R; Isoppo, C; Quinaz Romana, G; Carvalho, D; Fernandes, A Campos
Abstract: Background: The use of transfusions leads to excessive blood consumption, implying risks such as infections and immunological reactions, so it should be used only when strictly necessary. Patient Blood Management (PBM) aims to minimize the use of allogeneic blood and improve clinical outcomes, with better cost-effectiveness, using three essential points: improving hematopoiesis, minimize blood loss in and optimize the hemoglobin reserves of each patient. The aim of this work is to assess the preoperative haemoglobin optimization using ferric carboxymaltose as part of PBM implementation, in elective orthopaedic, cardiac and colorectal surgery in Portuguese hospitals. Methods: This is an observational study materialized in a retrospective and multicenter cohort with data collection from medical records. The population and sample will be patients over 18 years from elective orthopaedic, cardiac and colorectal surgeries, treated according with local standards before PBM implementation were assigned to the pre-PBM cohort and patients after PBM implementation with ferric carboxymaltose to preoperative haemoglobin optimization to the PBM cohort. The criteria for selecting hospitals will be the implementation of PBM during the study period. Expected Results: Based on a previous review, it is expected that the results of the use of ferric carboxymaltose to correct iron deficiency anaemia for preoperative haemoglobin optimization will contribute positively to reducing the number of transfusions, the length of hospital stays and will have a direct impact on economic results. Conclusions: The use of ferric carboxymaltose and other ferric compounds, as part of PBM program, has demonstrated a positive impact on patients' outcomes (morbility and mortality), adverse events and on economic results. This study might show that clinical guidelines and programs like PBM are a major contribution not just for hemovigilance and blood safety but also for patient safety and health quality. Key messages: This work is focused on Portuguese hospitals and aims to assess the impact of ferric carboxymaltose and its benefit on PBM strategy. Specially this study intends to conduct the assessment on health outcomes and costs.